2011
DOI: 10.1007/s10658-011-9745-y
|View full text |Cite
|
Sign up to set email alerts
|

PCR-SSCP analysis of Fusarium diversity in asparagus decline in Japan

Abstract: The diversity of Fusarium populations in asparagus (Asparagus officinalis L.) decline fields in Japan was estimated by PCR-SSCP (single-stranded conformational polymorphism) analysis of the ITS2 regions of the nuclear rRNA genes. This method was used to rapidly and objectively identify pathogens associated with roots of plants showing symptoms of asparagus decline collected from fields in five regions across Japan. Over 651 fusarial isolates were obtained, and were easily differentiated into three principal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The epidemiology of other toxigenic fungi like Fusarium spp. is well investigated to assess spatial and temporal distribution of these economically important phytopathogens (Bentley et al 2008;Nahiyan et al 2011;Beyer et al 2014) and other fungal genera (Lumbsch et al 2008;€ Opik et al 2013). Pasquali and Migheli (2014) summarized the persistence and spread of Fusarium chemotypes worldwide and demonstrated regional differences, spatial chemotype diversity and the influence of environmental and cultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of other toxigenic fungi like Fusarium spp. is well investigated to assess spatial and temporal distribution of these economically important phytopathogens (Bentley et al 2008;Nahiyan et al 2011;Beyer et al 2014) and other fungal genera (Lumbsch et al 2008;€ Opik et al 2013). Pasquali and Migheli (2014) summarized the persistence and spread of Fusarium chemotypes worldwide and demonstrated regional differences, spatial chemotype diversity and the influence of environmental and cultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,8]. In Japan, Nahiyan et al [9] demonstrated that Fp and Foa are dominant Fusarium species in asparagus decline fields by PCR-SSCP analysis. However, the diseases are still difficult to control because no resistant cultivar or disinfesting method has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is exacerbated by a replant phenomenon such that additional loss is incurred if fields are replanted with asparagus (Blok and Bollen, 1995). A number of facts worldwide contribute to asparagus decline, but the most significant is crown and root rot caused by Foa and Fusarium proliferatum (Elmer et al, 1996;Knaflewski et al, 2008;Nahiyan et al, 2011;Reid et al, 2002;Wong and Jeffries, 2006). In addition, abiotic factors such as allelopathic residues can increase plant stress and accelerate the decline phenomenon (Lake et al, 1993;Miller et al, 1991;Yong, 1984).…”
mentioning
confidence: 99%